2019
DOI: 10.3389/fphys.2019.00479
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Redox-Imbalance in Rett Syndrome Affects Mitochondria as Well as Cytosol, and Is Accompanied by Intensified Mitochondrial O2 Consumption and ROS Release

Abstract: Rett syndrome (RTT), an X chromosome-linked neurodevelopmental disorder affecting almost exclusively females, is associated with various mitochondrial alterations. Mitochondria are swollen, show altered respiratory rates, and their inner membrane is leaking protons. To advance the understanding of these disturbances and clarify their link to redox impairment and oxidative stress, we assessed mitochondrial respiration in defined brain regions and cardiac tissue of male wildtype (WT) and MeCP2-deficient ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 74 publications
(160 reference statements)
5
37
0
9
Order By: Relevance
“…However, mitochondria are the main source of ROS generation. 43 Some researchers reported that the increased ROS generation in Rett mice was accompanied by increased mitochondrial activity. 4,44 MMP contributes to the systemic oxidative burden and oxidative tissue damage in CHANG and HuH-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, mitochondria are the main source of ROS generation. 43 Some researchers reported that the increased ROS generation in Rett mice was accompanied by increased mitochondrial activity. 4,44 MMP contributes to the systemic oxidative burden and oxidative tissue damage in CHANG and HuH-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in isolated mitochondria from the hippocampus and cortex of Mecp2 -KO mice indicated that hippocampal and cortical mitochondria are impaired as they release more ROS and consumed more O 2 compared to WT littermates [ 144 ]. Still, it is unclear if the mitochondrial defects found in these disease models can be solely attributed to increased respiration and if these alterations are the consequence of redox imbalances.…”
Section: Asd-related Neurodevelopmental Disordersmentioning
confidence: 99%
“…They are summarized and graphically presented in Figure 1. RI increases mitochondrial ROS production by upregulating the activities of complexes I to IV [16] and impacts the NAD + /NADH balance leading to damage to lipids, proteins [17,18], and DNA [19]. Impaired oxidation of NADH to NAD + by the electron transport chain (ETC) is an adaptive mechanism of hypoxia, analogous to the "hypoxia-like" RI resulting from increased flux of glucose [20,21].…”
Section: Redox Imbalance (Ri) and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Reductive stress, first introduced in 1987 [10], is described as an excess of reducing equivalents, in the forms of NAD(P)H and/or glutathione, in the presence of intact oxidoreductive Figure 1: Interrelationship between RI and mitochondrial dysfunction. NAD + /NADH imbalance is the main cause leading to lipids, proteins, and DNA damage and triggering the increase in ROS production by the electron transport chain [16][17][18][19]. ROS are metabolic by-products generated by mitochondria that can damage macromolecules by structurally altering protein amino acids leading to formation of protein carbonyls, DNA mutation (e.g., single-and double-strand breaks, inter/intrastrand cross-links, and DNA-protein cross-links), and lipid peroxidation [29,30].…”
Section: Reductive Stress-induced Mitochondrial Dysfunctionmentioning
confidence: 99%